Derivas da comunicação: a cidade pelo olhar da artemídia - Costa, Daniela (2007)
Dérive: a way of experimental behavior that is linked to the urban society conditions: a technique of rapid passage through varied ambiances. More particularly, it is also said to designate the duration of an ongoing exercise from this experience . This definition is found in a declaration made in 1958 by the Situationist International. By registering their experiences with photographs, texts and films, the situationists roamed about the city in search of empty spaces , places that had no meaning at least in touristic or architectonic terms, but the situationists liked them so much. Today the city is more a hypertext than a paste-up. It is an entanglement of ways that are bifurcated, and flows concerning information and communication, transport, capital pass through these ways where there are human beings are nearly always in motion, either by choice or need. In this context, it comes up an other form of dérive that makes use of the city technological apparatus such as electronic panels and communication networks GPS, laptops, cell phones and virtual simulators to map the city, creating collective, multilinear urban narratives and stimulating the mobility. These artistic manifestations are the study purpose of this research that is characterized as a depiction on dérive while being artistic practice